P.K. Pinkerton and the pistol-packing widows - Lawrence, Caroline (Lawrence, Caroline. P.K. Pinkerton series, 2015)
In 1860s Nevada, master-of-disguise P.K. Pinkerton uncovers a sinister plot when he takes a case that calls for him to shadow his friend and mentor, Poker Face Jace.